2003
DOI: 10.5134/143423
|View full text |Cite
|
Sign up to set email alerts
|

<Review> Acquisition of Skilled Gathering Techniques in Mahale Chimpanzees

Abstract: Chimpanzees show a remarkable ability to organize actions into complex programs, shown most famously in their ability to employ tools in many different ways for subsistence. Chimpanzee tool use has been much studied, with an emphasis on the tool rather than the process of use. We planned instead to examine chimpanzee skills in the broader context of plant-processing techniques, with an emphasis on the process. In particular, we focused on the development of infants in parallel with describing the skills of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…This effect is difficult to interpret because it is proposed to be related to the smaller sample size with bouts than frequency, as significant biases are more likely to appear with large than small samples (Hopkins 2006;Hopkins et al 2001McGrew and Marchant 1997) (hypothesis tested and discussed in Chapelain and Hogervorst 2009). Our finding of strong laterality for bimanual manipulative coordination in bonobos is consistent with previous data on bimanual coordinated actions in bonobos and other species for the tube task and food-processing tasks (Byrne and Byrne 1991;Byrne and Corp 2003;Corp and Byrne 2004;Ingmanson 1998;Meguerditchian et al 2010). This supports hypotheses proposing that complex tasks that are crucial for survival, such as food processing that involves bimanual coordination, manipulation and precise actions, elicit laterality; and suggests that these actions may have been selective pressures for the emergence of handedness.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This effect is difficult to interpret because it is proposed to be related to the smaller sample size with bouts than frequency, as significant biases are more likely to appear with large than small samples (Hopkins 2006;Hopkins et al 2001McGrew and Marchant 1997) (hypothesis tested and discussed in Chapelain and Hogervorst 2009). Our finding of strong laterality for bimanual manipulative coordination in bonobos is consistent with previous data on bimanual coordinated actions in bonobos and other species for the tube task and food-processing tasks (Byrne and Byrne 1991;Byrne and Corp 2003;Corp and Byrne 2004;Ingmanson 1998;Meguerditchian et al 2010). This supports hypotheses proposing that complex tasks that are crucial for survival, such as food processing that involves bimanual coordination, manipulation and precise actions, elicit laterality; and suggests that these actions may have been selective pressures for the emergence of handedness.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to these external factors, sex and age should also be taken into account because they may influence laterality. For instance, several studies have found that males were more left-handed than females (e.g., Byrne and Corp 2003;Corp and Byrne 2004;Milliken et al 1991). Other studies have found that immature individuals exhibited weaker or less consistent preferences than adults, which indicates that laterality may increase with age, suggesting some maturation of hand preferences (e.g., Boesch 1991;Fletcher and Weghorst 2005;Hook and Rogers 2000;Hopkins 1994Hopkins , 1995Humle and Matsuzawa 2009;Milliken et al 1991;Vauclair and Fagot 1987;Suomi 1993, 1994).…”
mentioning
confidence: 95%
See 1 more Smart Citation